Comparison of graft uptake between tragal cartilage and temporalis fascia in type-I tympanoplasty - Noor, Allah; Nawaz, Hamza; Khan, Ali; Ahmad, Ijaz; Arif, Muhammad (International Journal of Pathology, 2025)
Background: To compare the anatomical success rates of type I tympanoplasty using tragal cartilage-perichondrium versus temporalis fascia grafts in patients with chronic suppurative otitis media. Methods: This prospective comparative study was carried out at Ear, Nose, Throat (ENT) Department Hayatabad Medical Complex Peshawar. The study comprised 115 patients with central tympanic membrane perforations. Patients were divided into two groups at random: Group B (n=57) received a tragal cartilage-perichondrium graft, while Group A (n=58) had tympanoplasty with temporalis fascia. All procedures were performed post auricularly utilizing the underlay technique while under general anesthesia. Anatomical transplant success three months after surgery was the main outcome measure. Results: The tragal cartilage group had a significantly higher graft uptake rate (86.2 Vs 96.5%) (p=0.047) than the temporalis fascia group. Sub-analysis of the 10 failures cases revealed that the majority (n=7) were caused by significant perforations, with 5 failures being explained by the line of the best fit passing through the temporalis fascia.Conclusion: The superior graft material for type I tympanoplasty is tragal cartilage-perichondrium, which has a significantly greater anatomical success rate than temporalis fascia. It should be considered the preferred graft for tympanic membrane restoration because it is the best choice, particularly for larger perforations.